Healing in a Social Context: The Importance of Clinician and Patient Relationship - Wampold, Bruce E. (Frontiers in Pain Research, 2021)
When a patient presents to a health provider, the course of the disorder is composed of three effects: natural effects, specific effects, and contextual effects. Part of the contextual effect is due to the relationship between the healer and the patient. Social healing appears to be present in eusocial species and particularly well developed in humans. Evidence for the importance of the relationship in healing is found in placebo studies, including placebo analgesics, medicine, and psychotherapy. Although the theory for how the relationship is therapeutic is not well developed, four possible mechanisms are discussed. The implications for health care and the treatment of pain are discussed.